Wheat genomic study for genetic improvement of traits in China - Jun Xiao; Liu, Bao; Yingyin Yao; Zifeng Guo; Haiyan Jia; Kong, Lingrang; Aimin Zhang; Wujun Ma; Zhongfu Ni; Xu, Shengbao; Fei Lu; Yuannian Jiao; et al. (Springer, 2022)
Bread wheat (Triticum aestivum L.) is a major crop that feeds 40% of the world’s population. Over the past several decades, advances in genomics have led to tremendous achievements in understanding the origin and domestication of wheat, and the genetic basis of agronomically important traits, which promote the breeding of elite varieties. In this review, we focus on progress that has been made in genomic research and genetic improvement of traits such as grain yield, end-use traits, flowering regulation, nutrient use efficiency, and biotic and abiotic stress responses, and various breeding strategies that contributed mainly by Chinese scientists. Functional genomic research in wheat is entering a new era with the availability of multiple reference wheat genome assemblies and the development of cutting-edge technologies such as precise genome editing tools, high-throughput phenotyping platforms, sequencing-based cloning strategies, high-efficiency genetic transformation systems, and speed-breeding facilities. These insights will further extend our understanding of the molecular mechanisms and regulatory networks underlying agronomic traits and facilitate the breeding process, ultimately contributing to more sustainable agriculture in China and throughout the world.